Readers' guide to periodical literature. (Bronx, N.Y. : H.W. Wilson, 1985)
"An author subject index to selected general interest periodicals of reference value in libraries."
At head of title: Wilsondisc.
Corresponds to the printed versions: Readers' guide to periodical literature; and: Readers' guide to periodical literature (Cumulative volume).
System requirements: IBM PC or fully compatible computer; 640K of memory; DOS 3.0 or higher; hard disk drive with at least 2 MB of free disk space; printer (optional); Hayes or fully compatible modem (optional).
Accompanied by installation disks and user guide.
Description based on: 1/83-10/31/91; title from disc label.
Latest issue consulted: 1/83-10/29/92.
Keywords: Periodicals -- Indexes; Periodicals; Indexes